Henna causes life threatening haemolysis in glucose-6-phosphate dehydrogenase deficiency. Issue 5 (1st November 2001) - Raupp, P; Hassan, J Ali; Varughese, M; Kristiansson, B
Abstract : Haemolytic crisis in glucose-6-phosphate dehydrogenase deficient individuals following topical application of henna occured in four children: a female neonate (haemoglobin 50 g/l, serum bilirubin 700 μmol/l), who recovered after exchange transfusion; a male infant (haemoglobin 28 g/l) who died despite transfusion; and two preschool children (haemoglobin 40 and 41 g/l respectively).